Effect of Systemic Soil Insecticides and a Plant Product on Microbial Load of Soil in Root (wilt) Affected Coconut Monocropping Ecosystem - Murali Gopal; Alka Gupta; P. Rajan; C.P. Radhakrishnan Nair (International Coconut Community Journal, 2001)
The changes undergoing in the microorganism population due to the application of phorate 10G, carbofuran 3G (@ 10 g a.i./ palm) and neem oil cake (@ 1.5 kg / palm) in the basin region of coconut growing in root (wilt) affected area was studied. Generally, a high microbial population was observed in the control plot. Carbofuran proved to be more toxic as compared to phorate as it suppressed the bacterial, actinomycetal, and free-living N2 -fixer’s number significantly. Against Nitrosomonas and Nitrobacter (nitrifiers), the influence was inconsistent. Neem oil cake enhanced bacterial and free-living N2-fixer count; against actinomycetes and fungi there was an initial stimulatory, and then antagonistic impact, whereas, it proved detrimental to the nitrifiers. From the six soil samplings done, spread over a period of six months, the microbial load was recorded to be high whenever there was moderate rainfall and medium temperature. Application of neem oil cake produced positive effect on the beneficial microorganisms as compared to the systemic insecticides.